A study effects of injection pressure and wall temperature on the mixing process of NOx and NH3 in Selective Catalytic Reduction system - Muhammad Khristamto Aditya Wardana; Ocktaeck Lim (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2020)
Diesel engines are commonly used for public transportation on-road and off-road applications. Growth production of the diesel engine is very significant from year to year. Nitride Oxide (NOx) from diesel engine was one of the major sources of air pollution. Selective Catalytic Reduction (SCR) has been successfully used to reduce NOx from a diesel engine with a chemical reaction from ammonia (NH3). The mixing reaction between NOx and NH3 reaction can produce steam (H2O) and Nitrogen (N2). However, ammonia uniformity pattern usually not homogenization and the ammonia was difficult to mix with NOx. The constant air flows incomplete to assist the spray injector to spread NH3 to all corners of SCR. The impact study of turbulent phenomena and standard k-epsilon Low-Reynolds Number model to the mixing process in the SCR system using STARCCM+. The simulation studies are conducted under different pressure (4 to 6 bars), the injection rate (0.04 g/s) and temperature (338 K – 553 K) and the high pressure and high velocity magnitude creating turbulent swirl flow. The ammonia decomposition process and mixing process with NOx were investigated using a box with optical access. The simulation and numerical study results validated using back pressure value and the distribution of NOx concentration value from the catalyst outlet. The wall temperature will increase the urea evaporation to generate ammonia and gas pressure will increase the mixing process and chemical process in the SCR system. These reactions enable to optimize the SCR system technology which eventually able to reduce the NOx quantity from a diesel engine.